Exploring English Teaching Practices in Orphanages: A Qualitative Study Using the Narrative Inquiry Approach - Agatsya, Titah; Hikmah , Nuril; Sandya, Yesika Agnes; Novitasari, Devi (English Language Teaching Methodology, 2025)
This study investigates English language teaching practices in orphanages, highlighting the lived experiences of volunteer educators in non-formal settings. Using a narrative inquiry approach at Mutiara Insan Orphanage, Banyuwangi, East Java, the research uncovers emotional, pedagogical, and contextual complexities in teaching under social and resource constraints. Data were gathered through participatory observation, narrative interviews, visual documentation, and literature review. Findings reveal that non-professional volunteers primarily use gamification to engage learners of diverse ages and proficiencies. Despite challenges such as limited resources, time, and inconsistent learner backgrounds, volunteers demonstrated adaptive, empathetic, and inclusive teaching practices. Notably, children showed gains in both basic English skills and socio-emotional confidence. This research offers a novel lens on English instruction in marginalized, under-researched contexts and underscores the urgent need for sustained pedagogical support and reflective practice in orphanage-based education.